Do ‘Ergatives’ Exist in Lycian? - Diether Schürr (Gephyra, 2018)
The Lycian word for ‘oath’, (tese/i-), being genus commune, should therefore not require an ‘ergative’ suffix of the kind attested in Hittite and Luwian, when a neuter is functioning as the subject of a sentence. On the contrary, the ‘collective’ (i.e. neuter) plural t[asa]: miñtaha (TL 75), ‘oaths of the Mindis’, is once attested as a punishing agency, as is marazija miñtaha (TL 118, 135 and 139), also neuter plural. The word tesẽti (TL 149) or teseti (TL 135), also a punishing agency, should signify ‘oath gods’, not ‘oaths’ personified, comparable with esbẽte, probably ‘horsemen’ (dative), and the theonym So(u)mendis.